2020
DOI: 10.48550/arxiv.2007.02947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-defect Dynamics in Active Nematics

Abstract: Recent experiments and numerical studies have drawn attention to the dynamics of active nematics. Two-dimensional active nematics flow spontaneously and exhibit spatiotemporal chaotic flows with proliferation of topological defects in the nematic texture. It has been proposed that the dynamics of active nematics can be understood in terms of the dynamics of interacting defects, propelled by active stress. Previous work has derived effective equations of motion for individual defects as quasi-particles moving i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 29 publications
(66 reference statements)
3
50
3
Order By: Relevance
“…Since −1/2 defects have a three-fold symmetry, ±1/2 defectpairs in active nematics generically unbind at low noise strengths [86]. While a full examination of defect dynamics in the interfacial nematic phase, including their advection by the active flow leading to non-reciprocal defect interactions [13,91], is beyond the scope of this paper, I now argue that the long-range interaction that stabilises the ordered phase to director fluctuations also makes the separation of ±1/2 defect much less likely than in other active nematic systems, both wet and dry.…”
Section: B Defect Interactions In the Nematic Phase Of Nnc Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Since −1/2 defects have a three-fold symmetry, ±1/2 defectpairs in active nematics generically unbind at low noise strengths [86]. While a full examination of defect dynamics in the interfacial nematic phase, including their advection by the active flow leading to non-reciprocal defect interactions [13,91], is beyond the scope of this paper, I now argue that the long-range interaction that stabilises the ordered phase to director fluctuations also makes the separation of ±1/2 defect much less likely than in other active nematic systems, both wet and dry.…”
Section: B Defect Interactions In the Nematic Phase Of Nnc Modelmentioning
confidence: 99%
“…ii. In addition to this, defects in an active system are also dragged by the velocity field generated by other defects [95] which leads to non-reciprocal interaction between defects [13,91,96]. A consideration of these complexities will be discussed elsewhere.…”
Section: B Defect Interactions In the Nematic Phase Of Nnc Modelmentioning
confidence: 99%
“…Recent work has focused on formulating an effective description of defects in active nematics as quasiparticles [18,25,19,21,26,20,27,28]. This approach parallels wellestablished work in equilibrium systems, where defects can be described as a gas of Coulomb charges and are known to drive order-disorder transitions in 2D [29].…”
Section: Introductionmentioning
confidence: 99%
“…Shankar et al [20] have shown that the dynamics of the gas of unbound defects can be mapped onto that of a mixture of self-propelled (the +1/2 defects) and passive (the −1/2 defects) quasiparticles with Coulomb interactions and aligning torques, provided that the texture gradients generated at the core of one defect by the other defects can be treated as quasistationary. More recently, the inclusion of multi-defect interactions, within the same quasistatic approximation, has revealed new non-central and non-reciprocal forces in multi-defect textures [28]. Important corrections to the effective dynamics also arise from the fact that the phase field induced at the core of a defect by all the others depends on all the defect velocities, as well as on their past history of accelerations, but including such effects remains a formidable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Active nematics have drawn considerable interest, and a general understanding of their behavior has begun to emerge from observations across a wide range of experimental systems that include in vitro assemblies of filamentous proteins [8][9][10][11], dense suspensions of elongated bacteria [12,13], living nematics [14], and dense colonies of elongated cellular tissues [15][16][17][18]. These experiments have been accompanied by theoretical studies that have sought to explain or anticipate their properties [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In active nematics, active stresses lead to a constant generation and annihilation of topological defects, giving rise to a loss of longrange nematic ordering.…”
mentioning
confidence: 99%